ANALISIS SEKTOR POTENSIAL DALAM MENETAPKAN PERENCANAAN PEMBANGUNAN DI KABUPATEN KARANGASEM - Dewi, Winda Savitri; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Effective and efficient development planning should be conducted once the potentials of each region are known. This research aims to determine and analyze the basic sectors and the potential sectors for development in Karangasem Regency. This research is conducted in Karangasem Regency and the data are obtained from Badan Pusat Statistik of Karangasem Regency and Bali Province. This research utilize the descriptive quantitative. This research use four analyses, namely the Location Quotient (LQ) analysis technique, Dynamic Location Quotient (DLQ) analysis technique, the Growth Ratio Model, the Overlay analysis and the qualitative analysis. The result of this research reveals that there are six basic sectors in Karangasem Regency, namely: the Agricultural, Forestry, and Fishery sector, Mining and Extraction, Transportation and Warehousing, Financial Service and Insurance, Public Administration, Defense and Mandatory Social Security, and other services. Potential sectors that can be developed in Karangasem Regency is the transportation sector and warehousing sector. Keywords : basic sector, potential sector, development planning.